The Different Brain Mechanisms of Object and Spatial Working Memory: Voxel-Based Morphometry and Resting-State Functional Connectivity - Ren, Zhiting; Zhang, Yao; He, Hong; Feng, Qiuyang; Bi, Taiyong; Qiu, Jiang (Frontiers in Human Neuroscience, 2019)
In working memory (WM), the ability to concurrently integrate different types of information and maintain or manipulate them promotes the flow of ongoing tasks. WM is a key component of normal human cognition. In this study, we applied a combined voxel-based morphometry (VBM) and resting-state functional connectivity (rsFC) analysis to investigate the relationship between the ability of object and spatial working memory (WM), and regional gray matter density (GMD), as well as intrinsic functional connectivity. The VBM analysis showed a positive correlation between the individual difference of object WM and GMD in the right middle occipital gyrus (MOG) and the left superior temporal gyrus (STG), which are responsible for coding object information and processing the shape of an object. The individual difference of the spatial WM was positively related to GMD in the right middle frontal gyrus (MFG) located in the dorsolateral prefrontal cortex (dlPFC), which confirmed that it is an important region for memory stores and maintains WM spatial representations. Further functional connectivity analysis revealed that the individual difference of object WM was significantly correlated with the rsFC of right intraparietal sulcus (IPS) – left postcentral gyrus (PostCG)/right precentral gyrus (PreCG)/left supplementary motor area (SMA). Whereas the capacity of spatial WM was significantly associated with the FC strength of left dlPFC – left precuneus, right dlPFC – right MFG, and left superior frontal sulcus (SFS) – left SMA/ right inferior parietal lobe (IPL). Our findings suggested that object WM is associated with the structure and functional organization of the brain regions involved in the ventral pathway (occipital - temporal regions) and the capacity of spatial WM is related to the dorsal pathway (frontal - parietal regions).